(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of this work was to obtain an overview of companies producing pellets from forest residual biomass of Santa Catarina, addressing characteristics related to raw material, equipment used, production costs, among other attributes that influence the dynamics of the state sector. Questionnaires were applied to each company participating in the study. The evaluated companies started their activities recently, the raw material is the wood of Pinus spp. With humidity between 8 and 10% and the equipment for pelletizing are adapted to biomass, damaging the process. The domestic market absorbed all the production and it was emphasized that the creation of a Brazilian standardization would be positive, especially with respect to the grades of pellet quality. It was also observed the lack of interaction between the three companies producing pellets, which hinders the growth of the pellet production chain in Santa Catarina.